Jail-Based Court Notifications to Improve Appearance Rates Following Early Pretrial Release - Foudray, Chelsea (American journal of criminal justice, 2023)
Pretrial reform efforts have facilitated earlier release of pretrial defendants, raising potential concerns about an increase in failure to appear (FTA) rates. Prior research has shown mixed, but generally positive, effectiveness of court notification strategies to reduce FTAs; however, to our knowledge, no study has examined this strategy for defendants released prior to charge filing. We conducted a retrospective, quasi-experimental investigation of the effectiveness of collecting contact information at the time of jail intake relative to practice as usual (i.e., court-based data collection and notification) on FTA outcomes. Participants were 527 pretrial defendants (205 intervention; 322 control) who received early release from jail between April 2018 through March 2019. Results showed jail-based notification was not associated with reduced likelihood of an FTA. However, the effect of jail-based notification on FTA was moderated by time to initial hearing, suggesting that jail-based collection of contact information may reduce FTA rates for initial hearings if the hearings are conducted in a reasonable timeframe following release. Our findings suggest a need for more research on court notification strategies overall and closer attention to the accessibility of notifications in the context of pretrial reform efforts.